Transport properties of perovskite-based stannate thin films of La-doped SrSnO3. (October 2021) - Kumar, Y.; Kumar, R.; Asokan, K.; Meena, R.; Choudhary, R.J.; Singh, A.P.
Abstract: SrSnO3 is a potential candidate for the perovskite-structured transparent electrode for many optoelectronic devices, especially for recently developed perovskite solar cells. La-doped SrSnO3 thin films were deposited using pulsed laser deposition on SrTiO3 (STO) substrate to study its structural and electrical properties. This study reveals that Lanthanum is a promising dopant for SrSnO3 . Results of the Rutherford backscattering experiment showed that the oxygen vacancies are increasing with strain on La doping. X-ray diffraction measurements revealed the increase in strain with La-doping which was the reason for the increase in oxygen vacancies. The charge-neutrality was maintained within the films by the reduction of Sn 4+ to Sn 2+ . The coexistence of two tin charge states (4+ and 2+) facilitated the hopping mechanism of the conduction. It was observed that La-doping reduced the electrical resistivity by 7 orders of magnitude with no significant change in its structure. Results obtained from X-ray absorption spectra are also consistent with these results. Highlights: La-doped SrSnO3 thin films on STO were studied for the structural, electrical and optical properties. La doping resulted in the enhancement in the electrical conductivity (up to 7 order). The improvement in the transport properties are due to the oxygen vacancies, La-doping, and hopping mechanism within the Sn states (4+ and 2+). The deposited films were highly transparent to visible light with a mobility of 40 cm 2  (V s) −1 .